Discursive strategies of legitimation on the web: Stakeholder dialogue in the agri-biotech industry. (October 2021) - Catenaccio, Paola
Abstract: The agrobiotechnology industry has been for over two decades at the centre of a heated debate. In the face of sustained criticism, agri-biotech companies have been mounting self-legitimising campaigns aimed at generating consensus around their core activities and their business practices. The controversy is primarily fought in the cybersphere, an arena which has been shown to exacerbate polarisation, but which also offers an opportunity for dialogue (cf. Williams et al., 2015). This study investigates selected aspects of the rhetorical web- and social media presence of Bayer CropScience, Syngenta and Monsanto. The latter no longer exists as an independent entity, but at the time of writing this article it still had an online presence and was included because of its importance in the history and development of the agri-biotech sector, where it pioneered highly orchestrated self-legitimation campaigns. The investigation looks at multiple sets of data: Q&A, FAQ and similarly structured sections on websites, Twitter communication, Facebook postings and related comments, and corporate websites as whole. Recent developments in the communication strategies adopted suggest growing awareness for dialogic engagement and webcare as part of a legitimation process which is conducted first and foremost rhetorically, and which relies extensively on argumentatively framed debates and responses (cf. Colleoni, 2013; Eberle et al., 2013; Kent and Taylor, 2016 ). The methodology adopted draws on discourse analysis and argumentation theory (Perelman and Olbrechts-Tyteca, 1969; van Eemeren and Grootendorst, 2004; Walton, 2007 ) to investigate macro-strategies of self-representation and patterns of dialogic interaction, including favoured argumentative schemes, pairing them with analyses at the meso- and micro-levels aimed at highlighting converging and competing pragmatic implications of linguistic choices. The findings suggest that dialogic engagement is challenging for companies operating in contested fields, and that monologic approaches to communication continue to prevail despite the companies' ostensible attempts to engage more openly and extensively with their publics. It is argued that discourse analysis and linguistics can usefully contribute to the development of effective strategies of stakeholder engagement.